Pendampingan Pengelolaan Wilayah Perbatasan di Indonesia: Lesson Learned dari KKN-PPM UGM di Kawasan Perbatasan - Djaka Marwasta (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2016)
The State of Republic of Indonesia is an archipelagic Country which has 17,508 islands (large and small), and has a very long perimeter border adjacently to neighboring countries, either in the land and sea. One of Municipality which is directly adjacent to the mainland of other countries is Merauke at Papua province. As a border region, Merauke has several functions, namely legal functions, control functions, and fiscal functions. At that time, these three functions are not going well in Merauke, even face many obstacles andto be an isolated regions. Some problems occurred in Merauke, among others: (1) has abundant natural resources (wet tropical forests, mineral wealth of gold, and abundant water resources), but has poor public accessibility; (2) socio-economic conditions are still low, particularly in accessing the basic needs (education, health); (3) unstable security of peoples; and (4) development policy (local, regional, national) were not in favor of local communities. This article is a summary of the several previous activities has be done, i.e. action research and the implementation of the KKN PPM UGM programs. The method used in these activities are observation and field surveys, focus group discussions, and the implementation of the KKN. Based on the several activities as mention before, the results that have been carried out are the general profile of border region and the typology of border region problems. To overcome these problems, it may take a very serious political will from the central and local governments, due torealized Merauke not just a backyard of the Indoensian Country.